Representations of Silence in Abbasid Poetry: A Pragmatic–Semantic Study of the Unspoken (The International Journal of Educational Sciences and Arts, 2025)
This study examines silence in Abbasid poetry as an active textual structure and a complex semantic strategy rather than a mere absence of speech. Adopting a pragmatic–semantic approach, the research integrates classical Arabic rhetorical theory—particularly the works of al-Jurjānī, al-Jāḥiẓ, and Ibn Rashīq—with modern discourse analysis to explore the mechanisms and functions of silence, including implication, allusion, strategic omission, and the unspoken. The analysis demonstrates that silence reshapes the poet–reader relationship by engaging the reader as a co-producer of meaning within politically and socially constrained contexts. It further reveals that silence functions pragmatically as a protective strategy against political authority through implicit satire and calibrated praise, aesthetically by generating rhythm and rhetorical pauses, and ethically and socially in ascetic and libertine poetry through suggestion, ambiguity, and controlled disclosure. The study concludes that silence in Abbasid poetry constitutes an independent semantic structure and a central expressive strategy that enriches poetic meaning and interpretive multiplicity, thereby warranting focused scholarly investigation within the study of classical Arabic literature.
Keywords: Silence; Abbasid Poetry; Pragmatics; Semantics; The Unspoken; Arabic Rhetoric; Power and Discourse